The causal effects of intelligence and fluid intelligence on Parkinson’s disease: a Mendelian randomization study - Jing, Cong; Zhong, Xiaojiao; Min, XuLi; Xu, Hao (Frontiers in Aging Neuroscience, 2024)
Parkinsons disease (PD) is a chronic neurodegenerative disease that affects the central nervous system, primarily the motor nervous system, and occurs most often in older adults. A large number of studies have shown that high intelligence leads to an increased risk of PD. However, whether there is a causal relationship between intelligence on PD has not yet been reported.In this study, mendelian randomization(MR) analysis was performed with intelligence (ebi-a-GCST006250) and fluid intelligence score (ukb-b-5238) as exposure factors and PD (ieu-b-7) as an outcome, which the datasets were mined from the IEU OpenGWAS database. MR analysis was performed through 3 methods (MR Egger, Weighted median, Inverse variance weighted (IVW)), of which IVW was the primary method. In addition, the reliability of the results of the MR analysis was assessed via the heterogeneity test, the horizontal polytropy test, and Leave-One-Out (LOO). Finally, based on Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, the genes corresponding to intelligence and fluid intelligence score related to SNPs were enriched for functional featuresfunctions and pathways.The results of MR analysis suggested that elevated intelligence indicators can increase the risk of PD (p=0.015, Odd Ratio (OR)=1.316). Meanwhile, fluid intelligence score was causally associated with the PD (p=0.035), which was a risk factor (OR=1.142). The reliability of the results of MR analysis was demonstrated by sensitivity analysis. Finally, the results of GO enrichment analysis for 87 genes corresponding to intelligence related SNPs mainly included regulation of synapse organization, developmental cell growth, etc. These genes were enriched in the synaptic vessel cycle, polycomb expressive complex in KEGG. Similarly, 44 genes corresponding to SNPs associated with fluid intelligence score were used for enrichment analysis. Based on the GO database, these genes were mainly enriched in regulation of developmental growth, negative regulation of neuron projection development, etc. In KEGG, 44 genes corresponding to SNPs associated with fluid intelligence scorethese genes were enriched in signaling pathways including Alzheimer disease, the cellular senescence, etc.The causal relationships between intelligence and fluid intelligence scores, and PD were demonstrated through MR analysis, providing an important reference and evidence for the study of PD.